Designing the Organizational Structure Model of Iranian Metropolitan Municipalities with a Comparative Approach to the Managerial Patterns of Developed Countries - Shehni, Arsalan; Amirnejad, Ghanbar; Taheri Ghoodarzi, Hojjat; Makvandi, Foad; Chenari, Vahid (Future of Work and Digital Management Journal, 2024)
The present study was conducted with the aim of designing a model of organizational structure for the municipalities of Iranian metropolises, using a comparative analysis of managerial patterns in developed countries. Considering the challenges in the current structure of municipalities, including centralization, weak interdepartmental coordination, and lack of utilization of modern technologies, this research seeks to propose an indigenous and efficient model for municipal structures by examining successful international cases. In the qualitative section, developed countries including Canada, the United States, Japan, and Germany were selected. In the quantitative section, the statistical population consisted of 40 individuals, among whom 20 participants were chosen through the snowball sampling method from university professors, metropolitan municipal officials, and city council members with master’s and doctoral degrees for conducting interviews. For model dimension development, 10 experts from this community were selected to participate in a focus group. Accordingly, the dimensions, components, and indicators of organizational structures in the municipalities of developed countries were first identified, and then their similarities and differences with the structures of Iranian municipalities were analyzed. Data were collected through documentary studies, comparative analysis, and expert opinions, and the proposed model was validated using qualitative methods. The findings of the study indicate that decentralized, participatory, and technology-oriented structures in developed countries play a significant role in enhancing the efficiency of urban management. Ultimately, the proposed model for the structure of Iranian metropolitan municipalities is presented, consisting of managerial levels, specialized units, participatory mechanisms, and technological infrastructures. This model can be employed as a practical solution in the path toward municipal structural reform and the realization of sustainable urban development.